PENGEMBANGAN MODEL KURIKULUM PENDIDIKAN EKONOMI UNTUK MENYIAPKAN GURU PROFESIONAL DI SEKOLAH BERTARAF INTERNASIONAL - Dadang Dahlan; Neti Budiwati; Susanti Kurniawati (Faculty of Economics, State University of Jakarta., 2013)
This study begins with a consideration of future challenges related to the need for international school teachers (SBI), which raises the question of how to design curriculum with competency-based approach in order to produce the teacher candidates that suit the needs of teachers in international schools (SBI )? The research objective is to be able to: 1) generate a description of strengths and weaknesses of curriculum designs that are being used; 2) produce a description of the implementation of a curriculum that is being implemented; and 3) produce a description of the competency standard (SKL) economics teacher candidates for international school (SBI) .The study was designed for 2 years using Research and Development, for the first year of this descriptive survey method, using the techniques of data collection in the form of documentation, questionnaires and interviews. The source data consists of lecturers, teachers, students and alumni who work at the international school (SBI). Among other results it was found that department of Economic Education curriculum has weaknesses and strengths. Weaknesses include a) the design curriculum not in accordance with the need to generate international school teachers (SBI); b) the design of the curriculum have not loaded the competencies required of graduates to compete at a global level; c) curriculum design has not adopted the curriculum developed countries that excel in the field of education. While its power is a) curriculum design approach based on scientific disciplines (content based); b) curriculum has been outlined in the syllabus and SAP; and c) curriculum design is flexible. Judging from the implementation of the curriculum, that has not been implemented based learning competency-based curriculum (KBK), but from the aspect of SBI implementation of curriculum-based learning (learning) already contains the necessary aspects of learning in SBI. Starting from the results of this study suggested: in the face of global challenges of the department of Economic Education is necessary to develop future curriculum design based CBC is consistently (consistently); implementation of the curriculum / learning must use a variety of approaches as expected by the curriculum, as well as to develop a curriculum thatcompliance-oriented international school teachers (SBI) must be rejected on the dotted-oriented curriculum development competency standards (SKL), which allows graduates can work in SBI and compete at a global level. Keywords: curriculum designs, competency-based, economic education